PENGARUH IMPLEMENTASI AKUNTANSI LINGKUNGAN TERHADAP KINERJA KEUANGAN DAN LINGKUNGAN PERUSAHAAN - Devi Puspita Sari; Ersi Sisdianto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to investigate the impact of environmental accounting implementation on a company's financial and environmental performance. Environmental accounting is an approach that integrates environmental considerations into the company's financial management. This research uses a quantitative method with a descriptive approach to analyze data obtained from companies that have implemented environmental accounting systems. The data used includes financial reports and environmental reports published by the companies during the study period. The findings indicate that the implementation of environmental accounting has a positive effect on the company's financial performance, reflected in improved profitability and operational cost efficiency. Additionally, companies that implement environmental accounting also show better environmental performance, evidenced by reduced negative environmental impacts and increased compliance with environmental regulations. This study contributes to the literature on accounting and environmental management by highlighting the importance of environmental accounting as a tool for achieving sustainable business goals.